Peranan perbankan syariah dalam meningkatkan kewirausahaan bagi pengusaha mikro - Binton Siburian; Bela Aprida; Parlin Tumpal Sinaga (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
One of the goals of financing in the micro sector is the distribution of excess fund, meaning that in people’s lives there are parties who have advantage while there are parties who lack. In relation to the problem of funds, the financing mechanism can be a brige in balancing and distributing excess fund from those who have excess funds to those who lack funds. The result of this research show that the reality that occurs today is that most Islamic banks provide financing not to the underprivileged who lack funds to open up business opportunities and crate business independene, but provide financing to people who already have business and are capable of entrepreneurship. However financing in Islamic banks has increased every year, this is the problem that wants to be studied